MENELAAH EKSISTENSI MANUSIA DALAM PEMIKIRAN VITALISME NIETZSCHE - Putri, Endrika Widdia (JURNAL AL-AQIDAH, 2021)
This paper examines the existence of humans in the vitalist thought of Nietzsche (1884–1900), one of the modern Western philosophers. This research is qualitative research using the descriptive analysis method. In this case, it attempts to describe and describe Nietzsche's vitalist thought and then analyzed it so that the desired results are obtained. This research shows data that in Nietzsche's view, the realization of the creativity of human existence is when humans can become the will to power "will to power" and this is the essence of humans being created on this earth. In Nietzsche's term, the human being whose existence is at its peak, he calls it ubermensch, namely man as the controller and determinant of his life, even the lives of others. Humans are free to do whatever they want to do. Even religion has no right to rule humans so that people live to rule each other. So, from that man has succeeded in utilizing his vital forces as a human..